Can MNCs promote more inclusive tourism? Apollo tour operator's sustainability work - Zapata Campos MJ; Hall CM; Backlund S (Taylor and Francis Group, 2018)
Outbound tour operators are key actors in international mass tourism. However, their contribution to more sustainable and inclusive forms of tourism has been critically questioned. Drawing from new institutional theories in organization studies, and informed by the case of one of the largest Scandinavian tour operators, we examine the corporate social responsibility (CSR) and sustainability work in large tour operators and the challenges faced in being more inclusive. On the basis of in-depth interviews with corporate officers, document analysis and media reports, we show how top-down coercive and normative pressures, coming from the parent company and the host society shape the ability of the daughter corporation to elaborate a more inclusive agenda. However, daughter companies do not merely comply with these institutional pressures and policy is also developed from the ‘bottom-up’. We show how the tour operator's sustainability work is also the result of organizational responses including buffering, bargaining, negotiating and influencing the parent organization. By creating intra and inter-sectoral learning and collaborative industry platforms, MNCs not only exchange and diffuse more inclusive practices among the industry, but also anticipate future normative pressures such as legislation and brand risk. Daughter organizations help shape their institutional arrangements through internal collaborative platforms and by incorporating local events and societal concerns into the multinational CSR policy, especially when flexible policy frameworks operate, and the corporate CSR agenda and organizational field are under formation. However, risks do exist, in the absence of institutional pressures, of perpetuating a superficial adoption of more inclusive practices in the mass tourism industry.
Keywords: Multinational corporations; tour operators; sustainable tourism; institutional theory; corporate social responsibility; sustainability work; human rights; labour rights